Evaluation of an intervention addressing a reablement programme for older, community-dwelling persons in Sweden (ASSIST 1.0): a protocol for a feasibility study. Issue 7 (24th July 2019) - Bergström, Aileen; Borell, Lena; Meijer, Sebastiaan; Guidetti, Susanne
Abstract : Introduction: Older persons with functional limitations often need assistance from home care staff to thrive and continue to live in their home environments. Reablement, a proactive, preventative approach administered by home care staff, stimulating active engagement of the older person, is often recommended. Even though reablement has a potential to become a new rehabilitation model and has been implemented in different countries in various degrees, there is a lack of knowledge regarding the process of establishing reablement, the theoretical underpinnings and the conditionality and outcomes in different contexts. This knowledge is needed before full-scale recommendations can be made for implementation in specific contexts. Aim: This study protocol aims to present a feasibility study of the intervention, ASSIST 1.0, a theory-based reablement programme, which includes coaching of home care staff and digitally based smart products, in a Swedish context. Methods and analysis: This feasibility study will evaluate the perceived value and acceptability of ASSIST 1.0 intervention programme regarding fidelity, reach and dose, and potential outcomes by using a pretest and post-test design involving an intervention group and a control group (n=30) of older persons living at home, needing home care services. Qualitative interviews with home care staff delivering ASSIST and the older adults receiving the intervention as well as their significant others will be conducted to explore aspects affecting the intervention. Ethics and dissemination: This study has been approved by the regional ethics board. The results of the feasibility study will form the base for refinement of the ASSIST programme and for the subsequent planning of a full-scale randomised controlled trial investigating the effect of the programme on a larger scale. Dissemination will include peer-reviewed publications and presentations at national and international conferences as well as information to involved stakeholders. Trial registration number: NCT03505619